Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Abused women and survivor therapy - Walker, Lenore E. (American Psychological Association, 2006)
Dans ce manuel de traitement de pointe, Lenore E. A. Walker soutient que les psychothérapies traditionnelles pour les victimes de traumatismes ont été insuffisantes pour traiter les femmes maltraitées. Alors que le problème de la violence à l'égard des femmes continue de tourmenter la société, couvrant tous les secteurs démographiques, Walker décrit des modifications essentielles à la pratique traditionnelle qui permettront aux praticiens de travailler plus efficacement avec les femmes victimes de violence. Ces modifications aboutissent à une compilation intégrée des stratégies d'évaluation et d'intervention les plus réussies, appelées « thérapie de survivant ». La thérapie des femmes maltraitées et des survivants discute des principales formes de violence subies par les femmes : viol et agression sexuelle, coups de feu, abus sexuels commis par des thérapeutes et discrimination/harcèlement sexuel sur le lieu de travail. Walker examine les effets du sexe, de la race, de l'ethnicité, de la culture et de l'orientation sexuelle sur chaque forme d'abus ; discute des considérations cliniques et des approches de traitement ; évalue les instruments d'évaluation couramment utilisés ; et analyse les problèmes médico-légaux dans les cas impliquant la violence contre les femmes. Walker soutient que les modèles de traitement réussis doivent tenir compte de l'impact spécifique des diverses formes d'abus, de la réponse psychologique unique de l'individu au monde, de l'impact de la socialisation traditionnelle des femmes et des hommes, et du transfert de thérapeutes et du contre-transfert. Ces considérations peuvent être appliquées au cours d'une thérapie qui cherche à réautonomiser les femmes maltraitées en les aidant à retrouver leur estime de soi, à rétablir des relations saines et à retrouver un sentiment de contrôle et de choix dans leur vie. La thérapie des femmes maltraitées et des survivants aide les praticien.nes nouvellement formé.e.s ainsi que le praticien.ne expérimenté.e à identifier, évaluer et traiter les femmes qui ont été maltraitées physiquement, sexuellement ou psychologiquement.
Keywords: approches et analyses; cours; discipline; intersectionnalité; psychologie; santé; santé mentale; sciences humaines; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis